14C Blank Assessment in Small-Scale Compound-Specific Radiocarbon Analysis of Lipid Biomarkers and Lignin Phenols. Issue 1 (23rd February 2020) - Sun, Shuwen; Meyer, Vera D; Dolman, Andrew M; Winterfeld, Maria; Hefter, Jens; Dummann, Wolf; McIntyre, Cameron; Montluçon, Daniel B; Haghipour, Negar; Wacker, Lukas; Gentz, Torben; van der Voort, Tessa S; et al.
ABSTRACT: Compound-specific radiocarbon ( 14 C) dating often requires working with small samples of < 100 µg carbon (µgC). This makes the radiocarbon dates of biomarker compounds very sensitive to biases caused by extraneous carbon of unknown composition, a procedural blank, which is introduced to the samples during the steps necessary to prepare a sample for radiocarbon analysis by accelerator mass spectrometry (i.e., isolating single compounds from a heterogeneous mixture, combustion, gas purification and graphitization). Reporting accurate radiocarbon dates thus requires a correction for the procedural blank. We present our approach to assess the fraction modern carbon (F 14 C) and the mass of the procedural blanks introduced during the preparation procedures of lipid biomarkers (i.e. n -alkanoic acids) and lignin phenols. We isolated differently sized aliquots (6–151 µgC) of n -alkanoic acids and lignin phenols obtained from standard materials with known F 14 C values. Each compound class was extracted from two standard materials (one fossil, one modern) and purified using the same procedures as for natural samples of unknown F 14 C. There is an inverse linear relationship between the measured F 14 C values of the processed aliquots and their mass, which suggests constant contamination during processing of individual samples. We use Bayesian methods to fit linear regression lines between F 14 C and 1/mass for the fossil and modern standards. The intersection points of these lines are used to infer F 14 Cblank and m blank and their associated uncertainties. We estimate 4.88 ± 0.69 μgC of procedural blank with F 14 C of 0.714 ± 0.077 for n -alkanoic acids, and 0.90 ± 0.23 μgC of procedural blank with F 14 C of 0.813 ± 0.155 for lignin phenols. These F 14 Cblank and m blank can be used to correct AMS results of lipid and lignin samples by isotopic mass balance. This method may serve as a standardized procedure for blank assessment in small-scale radiocarbon analysis.